TINDAKAN ABORSI BAGI KORBAN PEMERKOSAAN PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Siti Rahmawati Mega Tompunu; Zulfahmi Alwi; Hamzah Hasan (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
The point of this research is to find out how Abortion for Rape Victims Perspective of Positive Law and Islamic Law. The results of this study indicate that in Islamic law abortion is basically not allowed, because it kills the fetus which is considered sacred as a creation of Allah swt. According to positive law in Indonesia abortion is prohibited in the Criminal Code without any tolerance. KUHP as a general crime (Lex Generale), abortion is also regulated in Law no. 36 of 2009 concerning Health, articles 71-75 contain several indications that it is permissible to have an abortion. So PP No. 61 of 2014 concerning abortion due to rape as a more detailed elaboration of Law no. 36 of 2009. The view of Islamic law on Law no. 36 of 2009 and also PP No. 61 of 2014 does not violate religious rules and norms. The similarity of reasons is allowed because it is feared for the safety of the mother. In this PP, the safety of the mother is also prioritized, because if an abortion is not carried out, the mother's psyche will be disturbed. However, if she is not disturbed psychologically and accepts her pregnancy, then she cannot abort the pregnancy. If he does, he will be punished according to the rules. Keywords: Abortion, Rape, Positif Law, Islamic Law.